Spoken english for Saudi hajj volunteers : a needs assessment - Samer, Alanazi Khatmah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Saudi Arabia plays a vital role in hosting millions of Muslims during the Hajj season. The Saudi government provides hundreds of Hajj volunteers or Kashafah to assist the pilgrims in the two Holy places of Makkah and Madina. The majority of the pilgrims who come from different parts of the world are not well versed in Arabic. They either use English as an intermediary language or rely on body language to communicate. The Saudi Hajj volunteers, on the other hand, are native speakers of Arabic who are exposed to English as a foreign language in the Saudi school system. Communications between the pilgrims and the Saudi Hajj volunteers become a highly stressful task due to the fact that they speak in different languages. In view of the importance of English language proficiency among Saudi Hajj volunteers, the objective of the study is to investigate the spoken English language needs of Saudi Hajj volunteers in order to help them facilitate Hajj services. The study employs quantitative and qualitative research methodologies using a survey questionnaire and semi-structured interview. Both instruments were designed based on Rossett's (1982) question types. The questionnaire was distributed to 62 male Saudi Hajj volunteers, while a semi-structured interview was conducted with 11 Commanders volunteers from the Department of Education in Al Riyadh. The findings of the study indicate that the majority of Hajj volunteers are in need of a spoken English course to help them communicate effectively with the Pilgrims. Relevant recommendations and related to specific language functions and situations are provided.